Statistical moderation: A case study in grading on a curve - THULASIDAS, Manoj (Institutional Knowledge at Singapore Management University, 2021)
There is a negative perception about “grading on a curve,” because of the feeling that the cohort strength may skew the final grades one way or another. However, given the difficulties in ensuring absolute uniformity in assessment across the years, especially when taught and assessed by different instructors under different settings, grading on a curve may be a necessary evil. Once we accept this type of statistical moderation as the last line of defense in standardizing the final scores so that student cohorts from different terms or sections or schools may be compared, we have to implement it well. In this paper, we present the practice of grading on a curve as form of statistical moderation, and a moderation tool to achieve the objective behind the standardization of grades, the strategy and principles behind its implementation and our experiences with it.